COPD Case for Small Group Learning - Sara Bradley; Dennis Chang; Reena Karani (Association of American Medical Colleges, 2014)
Abstract Introduction This case was developed to be administered during an internal medicine-geriatrics clerkship with third-year medical students in a small-group setting of approximately 5-20 students to provide instructions on the diagnosis and treatment of chronic obstructive pulmonary disease. It is based on learning objectives from the Clerkship Directors in Internal Medicine-Society of General Internal Medicine Core Medicine Clerkship Curriculum and the American College of Physicians Guidelines for Diagnosis and Management of COPD. Methods The learners should be given the provided case in advance of the session and asked to prepare answers to the questions included with the case. There are suggested resources that learners can read in advance and use to prepare answers. The didactic portion should take one hour to complete. The room should be set up so that learners and facilitator can face each other, preferably sitting around a large table. During the session, we recommend that the facilitator call upon learners to read the case aloud and discuss the questions and answers. This allows for the learners to present the knowledge they gained during preparation and teach their colleagues. The facilitator acts to correct misinformation and keep the pace of the discussion, but the bulk of teaching should be done by the learners themselves. Results The rating of the session by approximately 140 clerkship students before and after implementation of the new case ranged from 3.24 to 3.75 on a 1 to 5 scale where 1 = unacceptable and 5 = superior. Discussion This product is used during one of four case-based didactic sessions facilitated by geriatrics fellows-in-training at our institution. Because the expectation is that the learners will prepare in advance and will do the bulk of the teaching themselves peer-to-peer, this product is an excellent resource to be used by new and less experienced educators such as fellows-in-training.